A kind of anti-friction lubricating aluminum alloy
By combining anodizing and physical sputtering molybdenum sulfide on the surface of the aluminum alloy, the problems of low roughness, high friction coefficient and poor corrosion resistance of the anodic film are solved, and the aluminum alloy surface with high corrosion resistance and high wear-reduction and lubrication performance are achieved.
Patent Information
- Application Number
- CN202110527775.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-05-14
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2041-05-14
AI Technical Summary
In the prior art, the anodic oxide film has low roughness, high friction coefficient and poor corrosion resistance, making it difficult to meet the needs of high corrosion resistance and high wear and reduction lubrication.
By performing anodizing treatment on the surface of the aluminum alloy, an anodizing film of 2-2.5 μm is formed, and molybdenum sulfide lubricating particles are physically sputtered in the pores of the film, combining hydrothermal treatment and polishing treatment to improve the density and roughness of the film.
High corrosion resistance and high wear-reduction lubrication performance are achieved, the friction coefficient is reduced to 0.2-0.3, and the roughness is between 1.7-2.3μm, which significantly improves the wear resistance and corrosion resistance of the aluminum alloy surface.
Smart Images

Figure CN113355713B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metal surface treatment, and in particular relates to a method for preparing highly corrosion-resistant, highly friction-reducing and lubricating aluminum oxide. Background Art
[0002] Aluminum alloy materials have been widely used in many industrial sectors such as electronics, electricity, aviation, chemicals, building materials, transportation, and daily life due to their excellent physical and chemical properties such as low specific gravity, excellent ductility, good electrical conductivity, strong corrosion resistance, and easy forming and processing. They have become the second largest category of metal materials used after steel. However, with the development of industrial technology, the performance requirements for materials are getting higher and higher. The inherent low hardness and poor wear resistance of aluminum alloys can no longer meet the increasingly demanding application conditions. This problem can be well solved through appropriate surface treatment processes. At present, improving the performance of aluminum alloys by continuously improving surface modification technology has become one of the hot spots in the theoretical and applied research of aluminum alloys. Aluminum alloy anodizing technology is the most widely studied and applied aluminum alloy surface technology.
[0003] Aluminum alloy will obtain a layer of aluminum oxide film on its surface through ordinary anodizing treatment. This film has good corrosion resistance and wear resistance, as well as a series of excellent physical and chemical properties, which improves the service life and application range of aluminum products. Therefore, it is known as "a universal surface film" for aluminum. By utilizing the porous characteristics of the anodized film and matching various special processes, different metal ions or organic substances are deposited in the film pores, giving the aluminum alloy surface more decorative or functional properties.
[0004] Since an anodic oxide film is formed on the surface of aluminum, the anodic oxide film has a porous and uneven structure. The oxide film layer exhibits a high friction coefficient under dry friction conditions, which not only increases friction power consumption, but also aggravates the wear of the two coupling materials, causing component failure. Therefore, the use of anodic oxide film to improve the friction reduction performance of ceramic film layers has been widely studied.
[0005] For example, CN201910935937A discloses a method for solidifying molybdenum disulfide film on the surface of aluminum alloy. First, a porous aluminum oxide film is generated on the surface of aluminum alloys such as 6061 by a secondary anodizing method, and then the molybdenum disulfide solid lubricant is introduced into the porous aluminum oxide film by radio frequency magnetron sputtering technology. The friction coefficient of the surface of aluminum alloys such as 6061 after solidification can be as low as 0.16, which is much lower than the friction coefficient of 6061 aluminum alloy of 1.10; the solid lubricant is deposited on the surface of the porous alumina film, which can be rubbed for 9750 times. The specific process is as follows: the 6061 aluminum alloy sheet is subjected to ultrasonic, chemical polishing and electrochemical polishing treatment, and then secondary pulse anodization is carried out in a 0.3 mol / L oxalic acid deionized water solution to form an alumina film with a regular porous array structure; the sample is taken out and rinsed with deionized water and dried; the aluminum sheet that has completed the secondary anodization is placed in a magnetron sputtering coating system, the sputtering time is set to 30 min, the sputtering temperature is set to 150 ° C, the sputtering power is 100 W, and the back vacuum is 5 × 10 -4 Pa, pre-sputtering time is 180s, and argon pressure is 2 Pa. After vacuuming, heating, pre-sputtering, pressure adjustment, sputtering, cooling to 50°C and taking out.
[0006] It can be clearly concluded from the drawings and preparation methods in the specification of the patent that the molybdenum sulfide completely covers the surface of the anodized film, that is, the main purpose of the patent is to "combine the porous array of aluminum oxide produced by anodization with the sputtered molybdenum disulfide lubricant to change the traditional way of combining the aluminum matrix with molybdenum disulfide", that is, all the physical and chemical properties of the composite material are provided by molybdenum sulfide, such as reducing the friction coefficient of the aluminum material, that is, the patent is only a simple superposition of the anodized film and molybdenum sulfide, which results in the corrosion resistance of the anodized film and the uniformity of the anodized array cannot be effectively exerted.
[0007] CN201110069772 discloses a method for making an aluminum alloy appearance part, which mainly includes the following steps: (1) stamping; (2) degreasing; (3) anodizing; (4) dyeing; (5) sealing. Compared with the prior art, the method for making an aluminum alloy appearance part of the present invention has the following advantages: the product has an anodizing color effect, a metallic high-gloss texture, and an appearance effect of a gradient color change; the surface of the product is not easy to fall off and rust by anodizing surface treatment, and the color is always as new; the surface of the product has high wear resistance and a warm and smooth feel; it provides a variety of product appearance options for industrial design to meet more consumer needs. The method for making an aluminum alloy appearance part provided by the present invention can be used to make appearance parts of various 3C products, especially laptop computers, tablet computers, mobile phones, and digital audio and video playback devices. In the step (5), the dyed aluminum alloy appearance part is immersed in a mixed sealing agent containing 0.3wt% nickel acetate and 0.3wt% molybdenum disulfide, and the sealing temperature is 90°C and the sealing time is 30min.
[0008] The patent introduces molybdenum sulfide during the sealing process of the anodized film in order to obtain a lubricating appearance effect. However, during the sealing process, molybdenum sulfide, as an inorganic additive particle, is almost coated inside the aluminum oxide film, that is, the friction reduction effect of molybdenum sulfide still needs to be improved.
[0009] CN201910070430A A method for preparing a high-friction-reducing lubricating nano-scale molybdenum disulfide coating for aluminum alloys, including a step of preparing a molybdenum disulfide electrophoretic solution, wherein the molybdenum disulfide electrophoretic solution is composed of a water-soluble resin, molybdenum disulfide, and distilled water; firstly, molybdenum disulfide is added to the water-soluble resin, and then distilled water is added to obtain the molybdenum disulfide electrophoretic solution; the aluminum workpiece after anodization is cleaned and placed in a molybdenum disulfide electrophoretic tank, in which a stainless steel plate or a lead plate is used as a cathode, and the aluminum workpiece after anodization is powered on, and the aluminum workpiece after anodization is used as an anode, so that the nano-scale molybdenum disulfide moves toward the aluminum workpiece after anodization, and a molybdenum disulfide coating is formed on the surface of the aluminum workpiece after anodization; the workpiece is taken out of the electrophoretic tank, and solidified in an oven to obtain a high-friction-reducing lubricating nano-scale molybdenum disulfide coating for aluminum alloys. The coating obtained by the method of the present invention is smooth, fine, has a small friction coefficient, strong adhesion, and good friction resistance.
[0010] The patent uses an electrophoretic method to coat organic matter and molybdenum sulfide on the anodized film. However, those skilled in the art know that when the aluminum material containing the anodized film is used as an electrode, its conductivity is significantly hindered. In addition, during the electrophoretic process, since the pores of the anodized film have been completely sealed, the bonding force between the electrophoretic paint and the anodized film is not strong. Summary of the invention
[0011] Based on the technical problems existing in the prior art, the purpose of the present invention is to provide a highly corrosion-resistant and highly anti-friction lubricating aluminum oxide to solve the problems of low roughness, high friction coefficient and poor corrosion resistance of the anodized film in the prior art, as follows:
[0012] A friction-reducing and lubricating aluminum alloy, wherein the surface of the aluminum alloy is an anodized film of 2-2.5 μm, the pores of the anodized film are in an array structure, the pore size is 500-600 nm, molybdenum sulfide lubricating particles are physically deposited inside the pores, and the aluminum alloy is at least subjected to anodizing treatment, physical sputtering molybdenum sulfide treatment, hydrothermal treatment and polishing treatment, and the obtained aluminum alloy surface has a roughness of 1.7-2.3 μm and a friction coefficient of 0.2-0.3.
[0013] In some embodiments, a pretreated aluminum alloy is used as the anode, an inert metal is used as the cathode, an aqueous solution of 0.5-1wt.% phosphoric acid and 0.006-0.007M aluminum oxalate is used as the electrolyte, and a temperature-controlled cooling device is used to control the anodizing temperature to 23-25°C, the corresponding oxidation voltage to 160-190V, and the corresponding anodizing time to 3-5min.
[0014] In some embodiments, the annealing heat treatment and the electrochemical polishing treatment, the annealing heat treatment is 420-450 o The electrochemical polishing treatment is carried out in a solution of perchloric acid and anhydrous ethanol in a volume ratio of 1:3, at a temperature of 23° C., a voltage of 21 V, and a polishing time of 4 minutes.
[0015] In some embodiments, the expanded aluminum alloy is subjected to physical sputtering molybdenum sulfide treatment:
[0016] (a) Use a vacuum pump to evacuate to 1×10 -3 After 30 0.5 Pa, inert gas argon is introduced, the pulse bias power supply is started, the voltage is set at 700V-800V, and the sample surface is cleaned by ion bombardment sputtering for about 3-5 minutes.
[0017] (b) Reduce the pulse bias amplitude to 400-500 V and the frequency to 10 KHz-20 KHz, make the vacuum reach 0.6-0.8 Pa, turn on the molybdenum sulfide target, and the deposition time is 5-10 min.
[0018] In some embodiments, the pore expansion treatment uses phosphoric acid at a concentration of 4-5 wt.% and a duration of 30-40 min.
[0019] In some embodiments, the physically sputtered aluminum alloy substrate is placed in a hydrothermal reactor, the air in the hydrothermal reactor is removed, the temperature is increased to 170-180° C. at 2-3° C. / min for 1-2 h, and then naturally cooled.
[0020] In some embodiments, the polishing process is: polishing on a polishing machine using a polishing cloth at a peripheral speed of 10-15 m / s for 5-10 min.
[0021] A friction-reducing and lubricating aluminum alloy, comprising the following processing steps:
[0022] (1) performing surface pretreatment on the aluminum alloy, wherein the heat treatment includes annealing heat treatment and electrochemical polishing;
[0023] (2) anodizing treatment, wherein the electrolyte used in the anodizing treatment is a mixed aqueous solution of phosphoric acid and aluminum oxalate;
[0024] (3) Hole expansion treatment, wherein the solution used in the hole expansion process is phosphoric acid.
[0025] (4) Physical sputtering of molybdenum sulfide;
[0026] (5) Hydrothermal treatment;
[0027] (6) Polishing treatment.
[0028] In some embodiments, the annealing heat treatment is performed at 420-450° C. for 3-5 hours.
[0029] In some embodiments, the electrochemical polishing process is carried out in a volume ratio of 1:3 between perchloric acid and anhydrous ethanol, at a temperature of 23° C., a voltage of 21 V, and a polishing time of 4 minutes.
[0030] In some embodiments, the anodizing parameters are: using a pretreated aluminum alloy as the anode, an inert metal as the cathode, an aqueous solution of 0.5-1wt.% phosphoric acid and 0.006-0.007M aluminum oxalate as the electrolyte, using a temperature-controlled cooling device to control the anodizing temperature to 23-25°C, the corresponding oxidation voltage to 160-190V, and the corresponding anodizing time to 3-5min.
[0031] In some embodiments, the pore expansion treatment uses phosphoric acid at a concentration of 4-5 wt.% and a duration of 30-40 min.
[0032] In some embodiments, the physical sputtering:
[0033] (a) Use a vacuum pump to evacuate to 1×10 -3 After 30 0.5 Pa, inert gas argon is introduced, the pulse bias power supply is started, the voltage is set at 700V-800V, and the sample surface is cleaned by ion bombardment sputtering for about 3-5 minutes.
[0034] (b) Reduce the pulse bias amplitude to 400-500 V and the frequency to 10 KHz-20 KHz, make the vacuum reach 0.6-0.8 Pa, turn on the molybdenum sulfide target, and the deposition time is 5-10 min.
[0035] In some embodiments, the hydrothermal treatment comprises placing the physically sputtered aluminum alloy substrate in a hydrothermal reactor, removing the air in the hydrothermal reactor, and heating the aluminum alloy substrate for 2-3 hours. o C / min increased to 170-180 o C hydrothermal treatment for 1-2h, and then naturally cool.
[0036] In some embodiments, the polishing process is performed using a polishing cloth on a polishing machine at a peripheral speed of 10-15 m / s for 5-10 min.
[0037] The aluminum alloy preparation process of the present invention is explained as follows:
[0038] First, the aluminum alloy is pretreated, annealing is used to remove stress, and polishing is used to remove the oxide film. The main purpose is to improve the orderliness of the pore array of the anodized film and obtain an anodized film with high bonding strength.
[0039] Secondly, anodization. It is known to those skilled in the art that the electrolyte used for anodization in the prior art is mainly sulfuric acid and oxalic acid. The use of the above acids can obtain a highly ordered nanopore structure with a pore size of generally 20-300 nanometers. However, it is difficult to obtain an anode pore with a pore size greater than 300 nm using the above acids. Although a porous AAO membrane with a larger pore spacing can be obtained in a phosphoric acid aqueous solution in the prior art, the order of the template is not high, and the system must be kept at a very low temperature so that the porous AAO membrane will not be broken down. This requires a very complex cooling device. The present invention effectively suppresses the oxidation current and increases the oxidation voltage by adding aluminum oxalate to a single phosphoric acid electrolyte. Specifically, by using Al 3+ Complex with oxalic acid to reduce Al in solution 3+ The migration rate can balance the H+ generated by water ionization to ensure the oxidation process, that is, effectively buffer the anodizing process to obtain large-aperture anodizing channels. By controlling the voltage, temperature and time during the anodizing process, the pore size of the anodized film channels is 300-400nm, and the thickness of the anodized film is about 2-3 microns. Figure 1 and attached Figure 2 shown.
[0040] Then, the pores are expanded by immersion in phosphoric acid. Due to process limitations, the present invention expects to obtain a large-aperture channel array directly by anodization, but the pore size cannot be further expanded. If the pore size is too small, the subsequent physical sputtering cannot lubricate the molybdenum sulfide and cannot enter the pores. This requires pore expansion. The phosphoric acid concentration used for the pore expansion treatment is 4-5wt.%, the time is 30-40min, and the pore expansion speed is 1.5-2nm / min. The pore size of the obtained channel is 500-600nm, as shown in the attached Figure 3 As shown, attention should be paid to controlling the hole expansion time. If the time is too long, such as exceeding 150 minutes, this will cause the unsealed anodized film to be completely corroded and dissolved.
[0041] Then physical sputtering is performed to deposit molybdenum sulfide in the pores of the oxide film. The deposition rate of physical sputtering should be controlled to avoid excessive deposition and insufficient deposition. The deposition time is 5-10 minutes. Under the conditions, the thickness of physical sputtering is usually about 2 microns, which is consistent with the thickness of the anodized pores. In addition, if excessive corrosion occurs, polishing can be performed after physical sputtering to remove excess molybdenum sulfide and expose the anodized film, otherwise it will affect the subsequent hydrothermal process.
[0042] During the physical sputtering process, there will inevitably be gaps between molybdenum sulfide and the inner wall of the pore, which cannot be completely filled. Through hydrothermal treatment, similar to the steam sealing treatment, the aluminum oxide is hydrothermally converted into hydrated aluminum oxide AlOOH. The volume will increase by about 30% in this process, which can effectively seal the gap between molybdenum sulfide and the inner wall of the pore, ultimately improving the density of the anodized film.
[0043] Finally, the substrate is polished and ground. Due to the hydrothermal expansion during the hydrothermal process, part of the hydrated aluminum oxide is squeezed out from the gap. Figure 4 As shown in the figure, the roughness of the oxide film surface increases greatly, and polishing is required to improve the roughness of the oxide film, which is 1.7-2.3μm. Figure 5 shown.
[0044] Beneficial technical effects: (1) The present invention obtains large-diameter and uniform-sized anodized pores through anodization and pore expansion.
[0045] (2) Molybdenum sulfide is deposited in the macropore channels by physical deposition. The molybdenum sulfide can be uniformly deposited in the macropore channels. However, there are gaps between the pore walls and the molybdenum sulfide, and the density of the anodized film needs to be improved.
[0046] (3) Through hydrothermal treatment, alumina hydrothermally expands, effectively filling the gap between molybdenum sulfide and the pore wall, thereby improving the density of the anodized surface;
[0047] (4) Through subsequent polishing, the roughness of the anodized film surface is improved to 1.7-2.3μm.
[0048] (5) The molybdenum sulfide is distributed in the pores of the anodic oxide film in an array shape, and the entire oxide film has high anti-friction and lubrication properties, with a friction coefficient of 0.2-0.3. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] Attached Figure 1 This is a SEM image of anodized aluminum alloy of the present invention.
[0050] Attached Figure 2 This is an enlarged SEM image of the anodized aluminum alloy of the present invention.
[0051] Attached Figure 3 This is the SEM image of the aluminum alloy subjected to hole expansion treatment according to the present invention.
[0052] Attached Figure 4 This is the SEM image of the aluminum alloy subjected to the hydrothermal treatment of the present invention.
[0053] Attached Figure 5 This is a SEM image of the polished aluminum alloy of the present invention. DETAILED DESCRIPTION
[0054] The present invention is further described in detail below in conjunction with specific embodiments, which are intended to explain the present invention rather than to limit it. Example 1
[0055] A friction-reducing and lubricating aluminum alloy is prepared by the following method:
[0056] (1) The aluminum alloy is subjected to surface pretreatment, wherein the heat treatment includes annealing heat treatment and electrochemical polishing.
[0057] The annealing heat treatment: at 420 o C for 3 h.
[0058] The electrochemical polishing treatment is carried out in a volume ratio of 1:3 between perchloric acid and anhydrous ethanol, at a temperature of 23° C., a voltage of 21 V, and a polishing time of 4 minutes.
[0059] (2) Anodizing treatment, wherein the electrolyte used in the anodizing treatment is a mixed aqueous solution of phosphoric acid and aluminum oxalate.
[0060] The anodizing parameters are as follows: using the pretreated aluminum alloy as the anode, the inert metal as the cathode, an aqueous solution of 0.5wt.% phosphoric acid and 0.006M aluminum oxalate as the electrolyte, using a temperature-controlled cooling device to control the anodizing temperature to 23°C, the corresponding oxidation voltage to 160V, and the corresponding anodizing time to 3min.
[0061] (3) Hole expansion treatment, wherein the solution used in the hole expansion process is phosphoric acid.
[0062] The phosphoric acid concentration used in the pore expansion treatment is 4 wt.% and the time is 30 min.
[0063] (4) Physical sputtering of molybdenum sulfide.
[0064] (a) Use a vacuum pump to evacuate to 1×10 -3 After 30 0.04 Pa, inert gas argon was introduced, and the pulse bias power supply was started with the voltage set at 700 VV, and the sample surface was cleaned by ion bombardment sputtering for about 3 minutes.
[0065] (b) Reduce the pulse bias amplitude to 400 V and the frequency to 10 kHz, so that the vacuum reaches 0.6 Pa, turn on the molybdenum sulfide target, and the deposition time is 5 min.
[0066] (5) Hydrothermal treatment.
[0067] The aluminum alloy substrate after physical sputtering was placed in a hydrothermal reactor, the air in the hydrothermal reactor was removed, and the temperature was raised to 170°C at 2°C / min. o C hydrothermal treatment for 1 h, and then naturally cooled.
[0068] (6) Polishing treatment.
[0069] The polishing process is performed by using a polishing cloth on a polishing machine at a peripheral speed of 10 m / s for 5 minutes. Example 2
[0070] A friction-reducing and lubricating aluminum alloy is prepared by the following method:
[0071] (1) The aluminum alloy is subjected to surface pretreatment, wherein the heat treatment includes annealing heat treatment and electrochemical polishing.
[0072] Annealing heat treatment: at 435 o C for 4 h.
[0073] The electrochemical polishing treatment is carried out in a volume ratio of 1:3 between perchloric acid and anhydrous ethanol, at a temperature of 23° C., a voltage of 21 V, and a polishing time of 4 minutes.
[0074] (2) Anodizing treatment, wherein the electrolyte used in the anodizing treatment is a mixed aqueous solution of phosphoric acid and aluminum oxalate.
[0075] The anodizing parameters are as follows: using the pretreated aluminum alloy as the anode, the inert metal as the cathode, using an aqueous solution of 0.75wt.% phosphoric acid and 0.0065M aluminum oxalate as the electrolyte, and using a temperature control cooling device to control the anodizing temperature to 24 oC, the corresponding oxidation voltage is 175 V, and the corresponding anodization time is 4 min.
[0076] (3) Hole expansion treatment, wherein the solution used in the hole expansion process is phosphoric acid.
[0077] The phosphoric acid concentration used in the pore expansion treatment is 4.5 wt.% and the time is 35 min.
[0078] (4) Physical sputtering of molybdenum sulfide.
[0079] (a) Use a vacuum pump to evacuate to 1×10 -3 After 30 0.04 Pa, inert gas argon was introduced, the pulse bias power supply was started, the voltage was set at 750 V, and the sample surface was cleaned by ion bombardment sputtering for about 4 minutes.
[0080] (b) Reduce the pulse bias amplitude to 450 V and the frequency to 15 kHz, so that the vacuum reaches 0.7 Pa, turn on the molybdenum sulfide target, and the deposition time is 7.5 min.
[0081] (5) Hydrothermal treatment.
[0082] The aluminum alloy substrate after physical sputtering was placed in a hydrothermal reactor, and the air in the hydrothermal reactor was removed. o C / min increased to 175 o C hydrothermal treatment for 1.5 h, and natural cooling.
[0083] (6) Polishing treatment.
[0084] The polishing process is performed by using a polishing cloth on a polishing machine at a peripheral speed of 12.5 m / s for 7.5 min. Example 3
[0085] A friction-reducing and lubricating aluminum alloy is prepared by the following method:
[0086] (1) The aluminum alloy is subjected to surface pretreatment, wherein the heat treatment includes annealing heat treatment and electrochemical polishing.
[0087] Annealing heat treatment: at 450 o C for 5 h.
[0088] The electrochemical polishing treatment is carried out in a volume ratio of 1:3 between perchloric acid and anhydrous ethanol, at a temperature of 23° C., a voltage of 21 V, and a polishing time of 4 minutes.
[0089] (2) Anodizing treatment, wherein the electrolyte used in the anodizing treatment is a mixed aqueous solution of phosphoric acid and aluminum oxalate.
[0090] The anodizing parameters are as follows: using the pretreated aluminum alloy as the anode, the inert metal as the cathode, an aqueous solution of 1wt.% phosphoric acid and 0.007M aluminum oxalate as the electrolyte, using a temperature-controlled cooling device to control the anodizing temperature to 25°C, the corresponding oxidation voltage to 190V, and the corresponding anodizing time to 5min.
[0091] (3) Hole expansion treatment, wherein the solution used in the hole expansion process is phosphoric acid.
[0092] The phosphoric acid concentration used in the pore expansion treatment is 5 wt.% and the time is 40 min.
[0093] (4) Physical sputtering of molybdenum sulfide.
[0094] (a) Use a vacuum pump to evacuate to 1×10 -3 After 30 0.5 Pa, inert gas argon was introduced, the pulse bias power supply was started, the voltage was set at 800 V, and the sample surface was cleaned by ion bombardment sputtering for about 5 minutes.
[0095] (b) Reduce the pulse bias amplitude to 500 V and the frequency to 20 kHz, so that the vacuum reaches 0.8 Pa, turn on the molybdenum sulfide target, and the deposition time is 10 min.
[0096] (5) Hydrothermal treatment.
[0097] The physically sputtered aluminum alloy substrate was placed in a hydrothermal reactor, the air in the hydrothermal reactor was removed, the temperature was raised to 180°C at 3°C / min for 2h, and then naturally cooled.
[0098] (6) Polishing treatment.
[0099] The polishing process is performed by using a polishing cloth on a polishing machine at a peripheral speed of 15 m / s for 10 minutes.
[0100] Comparative Example 1. A friction-reducing and lubricating aluminum alloy is prepared by the following method:
[0101] (1) The aluminum alloy is subjected to surface pretreatment, wherein the heat treatment includes annealing heat treatment and electrochemical polishing.
[0102] The annealing heat treatment: annealing at 435° C. for 4 hours.
[0103] The electrochemical polishing treatment is carried out in a volume ratio of 1:3 between perchloric acid and anhydrous ethanol, at a temperature of 23° C., a voltage of 21 V, and a polishing time of 4 minutes.
[0104] (2) Anodizing treatment, wherein the electrolyte used in the anodizing treatment is a mixed aqueous solution of phosphoric acid and aluminum oxalate.
[0105] The anodizing parameters are as follows: using the pretreated aluminum alloy as the anode, the inert metal as the cathode, an aqueous solution of 0.75wt.% phosphoric acid and 0.0065M aluminum oxalate as the electrolyte, using a temperature-controlled cooling device to control the anodizing temperature to 24°C, the corresponding oxidation voltage to 175V, and the corresponding anodizing time to 4min.
[0106] (4) Physical sputtering of molybdenum sulfide.
[0107] (a) Use a vacuum pump to evacuate to 1×10 -3 After 30 0.04 Pa, inert gas argon was introduced, the pulse bias power supply was started, the voltage was set at 750 V, and the sample surface was cleaned by ion bombardment sputtering for about 4 minutes.
[0108] (b) Reduce the pulse bias amplitude to 450 V and the frequency to 15 kHz, so that the vacuum reaches 0.7 Pa, turn on the molybdenum sulfide target, and the deposition time is 30 min.
[0109] Comparative Example 2. A friction-reducing lubricating aluminum alloy is prepared by the following method:
[0110] (1) The aluminum alloy is subjected to surface pretreatment, wherein the heat treatment includes annealing heat treatment and electrochemical polishing.
[0111] The annealing heat treatment: annealing at 435° C. for 4 hours.
[0112] The electrochemical polishing treatment is carried out in a volume ratio of 1:3 between perchloric acid and anhydrous ethanol, at a temperature of 23° C., a voltage of 21 V, and a polishing time of 4 minutes.
[0113] (2) Anodizing treatment, wherein the electrolyte used in the anodizing treatment is a mixed aqueous solution of phosphoric acid and aluminum oxalate.
[0114] The anodizing parameters are as follows: using the pretreated aluminum alloy as the anode, the inert metal as the cathode, an aqueous solution of 0.75wt.% phosphoric acid and 0.0065M aluminum oxalate as the electrolyte, using a temperature-controlled cooling device to control the anodizing temperature to 24°C, the corresponding oxidation voltage to 175V, and the corresponding anodizing time to 4min.
[0115] (5) Steam sealing treatment.
[0116] Use 100℃ steam for sealing for 5 minutes.
[0117] The comparative example 1 is similar to the preparation method in CN201910935937A, and the physical sputtering time used is 30 minutes as the sputtering time in Example 1 of the patent. Compared with the present application, there is no hole expansion treatment in the comparative example 1, the physical sputtering time of molybdenum sulfide is 30 minutes, and there is no hydrothermal and polishing treatment. The friction coefficient of the comparative document 1 is lower than that of the present application, similar to the friction coefficient of CN201910935937A <0.2. The neutral salt spray test is performed on the comparative example 1 and the example 2 in accordance with the standard of GB / T10125-2012: "Artificial atmosphere corrosion test (salt spray test)".
[0118] The time for obvious corrosion to appear in Example 2 is more than 1100h, the time for obvious corrosion to appear in Comparative Example 1 is about 450h, and the time for obvious corrosion to appear in Comparative Example 2 is more than 620h. The present invention effectively improves the density of the anodized film by filling the pores with molybdenum sulfide and sealing the pores by hydrothermal expansion, and has high salt spray resistance. In comparison, the aluminum material in Comparative Example 1 is anodized without any sealing treatment, and molybdenum sulfide is directly physically deposited thereon, and the molybdenum sulfide is a porous film, which makes the corrosion resistance of Comparative Example 1 poor, which is inferior to the aluminum alloy of Comparative Example 2 that is anodized and sealed.
[0119] In addition, ultrasonic thermal vibration experiments were carried out on Example 2 and Comparative Example 1. First, the samples were weighed and the samples to be tested were placed at 150 o C drying oven for 24h, then ultrasonically oscillate with a 100Hz deionized water solution for 20min, and finally blow dry with hot air, weigh, and calculate the mass loss. The mass loss rate of comparative example 1 is 47.5%, the mass loss rate of embodiment 2 is 9.5%, and the mass loss rate of the present application is only 3.1%, which further proves that the bonding force between the anodized film layer of the present invention and the aluminum material is strong.
[0120] The friction coefficient of Example 2 and Comparative Examples 1-2 was measured. The friction coefficient of Example 2 of the present invention was 0.2-0.3, and the roughness was 1.7-2.3 μm. The friction coefficient of Comparative Example 1 was 0.15-0.2, and the friction coefficient of Comparative Example 2 was 1.23, and the roughness was 3.5-4 μm.
[0121] Although the present invention has been described above by way of example with reference to the preferred embodiments, the present invention is not limited to such specific embodiments and can be appropriately modified within the scope of the protective scope of the present invention.
Claims
1. A friction-reducing lubricating aluminum alloy, characterized in that The surface of the aluminum alloy is an anodized film of 2-2.5 μm, the pores of the anodized film are array structures, the pore size is 500-600 nm, and molybdenum sulfide lubricating particles are physically deposited inside the pores. The aluminum alloy is at least anodized, expanded, physically sputtered with molybdenum sulfide, hydrothermally treated, and polished, and the obtained aluminum alloy surface has a roughness of 1.7-2.3 μm and a friction coefficient of 0.2-0.3; The phosphoric acid concentration used in the pore expansion treatment is 4-5wt.%, and the time is 30-40min; The aluminum alloy that has been expanded is physically sputtered with molybdenum sulfide: (a) Use a vacuum pump to evacuate to 1×10 -3 After 3000 Pa, inert gas argon is introduced, the pulse bias power supply is started, the voltage is set at 700V-800V, and the aluminum alloy surface is cleaned by ion bombardment sputtering for 3-5 minutes. (b) Reduce the pulse bias amplitude to 400-500 V and the frequency to 10 KHz-20 KHz, make the vacuum reach 0.6-0.8 Pa, turn on the molybdenum sulfide target, and the deposition time is 5-10 min.
2. The anti-friction lubricating aluminum alloy according to claim 1, characterized in that The anodizing treatment is as follows: using the pretreated aluminum alloy as the anode, the inert metal as the cathode, and an aqueous solution of 0.5-1wt.% phosphoric acid and 0.006-0.007M aluminum oxalate as the electrolyte, using a temperature control cooling device to control the anodizing temperature to 23-25°C, the corresponding oxidation voltage to 160-190V, and the corresponding anodizing time to 3-5min.
3. The anti-friction lubricating aluminum alloy according to claim 2, characterized in that The pretreatment includes: annealing heat treatment and electrochemical polishing treatment. The annealing heat treatment is annealing at 420-450° C. for 3-5 hours. The electrochemical polishing treatment is carried out in a perchloric acid and anhydrous ethanol solution with a volume ratio of 1:3, a temperature of 23° C., a voltage of 21V, and a polishing time of 4 minutes.
4. The anti-friction lubricating aluminum alloy according to claim 1, characterized in that The aluminum alloy substrate treated with physical sputtering molybdenum sulfide is placed in a hydrothermal reactor, the air in the hydrothermal reactor is removed, the temperature is increased to 170-180° C. at 2-3° C. / min for 1-2 hours, and then cooled naturally.
Citation Information
Patent Citations
Manufacturing method of aluminum alloy appearance piece
CN102691085A
Preparation method for high-antifriction lubrication nanoscale molybdenum disulfide covering layer for aluminum alloy
CN109576757A
Method for immobilizing molybdenum disulfide film on surface of aluminum alloy
CN110643940A